Patriotism among MARA University of Technology UiTM Machang branch students / Wan Fauzi Wan Mamat...[et al.] - Wan Mamat, Wan Fauzi; Yusof, Zulkarnain; Tuan Hassan, Tuan Mohd Rosli; Idrus, Maidin (University Publication Centre (UPENA), 2006)
Patriotism means strong feelings to love, respect and serve the country. This research was conducted to find the responsibility of the respondents as Malaysians and also about their knowledge of the historical background of the country. The main purpose of this study is to measure the level of patriotism among MARA University of Technology (UiTM) Machang branch students. The total number of respondents for this study is 300 from different faculties in UiTM Machang, Kelantan. Sampling technique used for the research was probability sampling. The Sampling chosen was stratified random sampling because it can minimize the possibility of classification errors. They were asked to evaluate their feelings of patriotism using structured questionnaire. The reliability analysis for each component produced a Cronbach Alpha between 0.751 and 0.942. The findings illustrates that 91.0% of the respondents are proud to be Malaysians. They wanted to know more about new historical material discovery. The respondents believe that loving the lyric of the song can increase their spirit 10 love this country. It showed that more females likes to visit the historical places.